Empreendedorismo informal digital e social commerce : um modelo de negócios no Instagram - Santana, Raísa Teixeira (2018)
Informal entrepreneurship is a worldwide phenomenon characterized by the heterogeneity of its activities, not being regulated by the government and, consequently, not paying the due taxes. Digital entrepreneurship has recently appeared due to the numerous technological changes and the advent of tools related to Information and Communication Technology (ICT), characterized by faster transactions and global reach. These advances have also enabled the emergence of social commerce, which is a business model based on the combination of the characteristics of virtual social networks and e-commerce sites for the sharing, purchase and sale of products and services. By combining both types of entrepreneurship, there is informal digital entrepreneurship that encompasses economic activities in the virtual environment, such as virtual social networks, which are not regulated by public authorities. With the intention of contributing to an exploration of this theme, this research aims at analyzing how informal digital entrepreneurship occurs through Instagram in Brazil. The research has a qualitative nature and it is exploratory and descriptive. Data of 15 clothing companies were collected through semi-structured interviews and non-participant observation. Subsequently, this data were analyzed through content analysis with the help of MAXQDA® software. The research results indicate that the profiles of business owners using Instagram as a channel to undertake are not so distinct, as most are women, with at least complete high school, with no previous experience with online business. Motivations such as ease of access to new markets, increased exposure of products and opportunity are among the most cited to start the venture. The difficulties most addressed were to achieve followers, only vision and sound can be used, bad functionalities and competition for prices, which are all linked specifically to the virtual environment. The relationship with customers and suppliers takes place in a face-to-face and virtual way, the latter being the most used. Although the enterprise exists in Instagram, this virtual social network is not the most used tool when it comes to interaction, in this case WhatsApp is the preference of both customers and suppliers. Regarding the average volume of sales, it was only possible to make estimates related to periods of high and low demand, since most of the respondents in this survey do not have a sales control. Despite this, it was possible to observe that even in the case of an investigation with only clothing companies each of them has its own particularities, which great influence of the sales volume of each one. The entrepreneurs surveyed have different perspectives and habits, not having the possibility to indicate the best or the worst way to undertake by Instagram or to score a precise and valid answer for all the informal digital entrepreneurs about how these ventures occur through Instagram in the Northeast. In addition, the great adaptability allows social commerce in Instagram to be used by several people with different characteristics. However, s-commerce is a recent phenomenon, and it is not possible to say whether the reality found in this research will prevail over the years.